Strategies for Building Religious Character in Schools - Fahmi, Fauzi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The quality of school graduates in the disruption era is now seen from its character. In research conducted with a qualitative approach. The type of research in this study uses a case study type multi site study design. In data collection techniques using techniques through: 1) Interview, 2) Observation and 3) Documentation. In data analysis using the theory of Miles and Huberman which consists of: 1) data collection, 2) sorting data, 3) presentation of data, 4) conclusion. The results of this study include: 1) The forms of religious character in SD Islamic Global School Malang and MI Miftahul Ulum Batu include: First, the Dimension of Faith (Aqidah). Second, the Dimensions of Worship Practices (Morals). 2) The strategy of religious character activities at SD Islamic Global School Malang and MI Miftahul Ulum Batu, among others: First, habituation. Second, exemplary. 3) The implications of the formation of religious character at SD Islamic Global School Malang and MI Miftahul Ulum Batu include: a) Fostering a spirit of worship and charity, b) Having a polite attitude towards others, c) Fostering social attitudes and a spirit of leadership for students.